Calibration of thermoluminescent detectors in H p (0.07) units by using an X-ray tube and a 137 Cs source - Małgorzata Wrzesień (Nofer Institute of Occupational Medicine, 2019)
Background The method of measuring doses based on the thermoluminescence phenomenon is not an absolute method. For this reason, to obtain correct results, it is necessary to calibrate detectors in the known radiation field. This paper presents a method for calibrating thermoluminescent detectors used in the measurement of personal dose equivalents (H p (0.07)) obtained by nuclear medicine facility personnel when handling the 99m Tc radionuclide. Material and Methods The authors used self-developed high-sensitivity thermoluminescent detectors and a HF320C X-ray unit, as well as a rod phantom. Dosimeters were calibrated in accordance with the ISO 4037-3 standard. During the measurements a vial containing a 99m Tc radionuclide with well-known activity was also used. The energy characteristics were supplemented by using a 137 Cs source (irradiator 60 Co/ 137 Cs). Results The value of the calibration coefficient for 118 keV energy energy was (1.90±0.02)×10 −5 mSv/imp. Taking into account the correction factor specified for of 140 keV energy at 0.962, the value of the calibration coefficient for 140 keV energy was determined as (1.83±0.02)×10 −5 mSv/imp. Conclusions Verification of the calibration coefficient determined for 140 keV energy carried out with a vial containing a 99m Tc radionuclide confirmed the correctness of the procedure. Med Pr. 2019;70(6):669-73